2017
DOI: 10.5152/tud.2017.76390
|View full text |Cite
|
Sign up to set email alerts
|

Infective complications in patients after transrectal ultrasound-guided prostate biopsy and the role of ciprofloxacin resistant Escherichia coli colonization in rectal flora

Abstract: Objective: In the present study, we aimed to invastigate the ciprofloxacin resistance in rectal flora of the patients undergoing prostate biopsy in our department. Additionally, the possible effects of the presence of ciprofloxacin resistant bacteria in faecal flora on the risk of infective complications after the procedure as well as the effect of antibiotic prophylaxis on such infectious complications have been evaluated. Material and methods:A total of 142 patients undergoing transrectal ultrasound-guided p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In a recent study, ciprofloxacin-resistant E. coli was detected in 53.5% of culture samples taken from rectal swabs before biopsy and resistant E. coli was observed in six of nine patients with high fever. Therefore, the authors stated that the antibiotic regimens should be amended (27) .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, ciprofloxacin-resistant E. coli was detected in 53.5% of culture samples taken from rectal swabs before biopsy and resistant E. coli was observed in six of nine patients with high fever. Therefore, the authors stated that the antibiotic regimens should be amended (27) .…”
Section: Discussionmentioning
confidence: 99%
“…Precisely targeted specimens from the appropriate cancerous foci should reduce the number of cores needed to diagnose. Furthermore, elastography might also decrease the number of biopsies per se and related complications [31]. Carneiro et al showed that a higher number of TRUS biopsy cores (>12) was associated with a higher risk of haemorrhage and perioperative complications during robotic-assisted radical prostatectomy [32].…”
Section: Elastography When and For Who?mentioning
confidence: 99%
“…The main source of urological infections after the biopsy is contamination and inoculation from rectal flora. Most patients scheduled for biopsy have a history of recurrent quinolone use [4] . Therefore, it is not surprising that the quinolone resistance of uropathogens is increased.…”
mentioning
confidence: 99%